Effect of palladium on photocatalytic activity of SnO2 nanoparticles - Janmanee R. (2014)
SnO2 nanoparticles were successfully synthesized with either the presence (PS) or absence (NPS) of the Broussonetia papyrifera (L.) Vent Pulp as the dispersant by the precipitation coupling with the thermal decomposition methods using tin tetrachloride pentahydrate (Sn4Cl.5H2O) and ammonium hydroxide (NH4OH) as the starting material and precipitant respectively. The pulp was soaked in SnCl4i solution and NH4OH was slowly added dropwise. The white gelable precipitate of Sn(OH)4 was obtained. Afterward, the white precipitate was filtered and washed until it was free from chloride. The white precipitate was then dried at 80°C for 24h and calcined for lh at 600°C, 650°C, and 700°C respectively. The synthesized products were characterized by X-ray diffraction (XRD), transmission electron microscope (TEM) and Brunauer-Emmett-Teller (BET) measurement of specific surface area. The crystallite sizes of SnO2 nanoparticles with the presence and absence of the pulp were found to be ranging from 5-15 nm and 5-30 nm respectively. The specific surface areas (SSABET) were 62.53 m2/g and 26.60 m2/g for PS and NPS samples respectively. SnO2 nanoparticles were doped with palladium in the range from 0.25-1.00 mol% by the impregnation method. The photocatalytic activity of SnO2 and Pd-doped SnO2 nanoparticles were investigated for the degradation of sucrose and glucose under UVA-light irradiation. The results showed that the photocatalytic activity of Pd-doped SnO2 was higher than pure SnO2 and the best photocatalytic activity for the degradation of sucrose and glucose were obtained in the case of Pd-doped SnO2 nanoparticles with 0.5 mol % and 1.0 mol % Pd loading respectively. © 2008 Trans Tech Publications, Switzerland.